(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Tourism represents a substantial and fast-growing sector of the economy of Uzbekistan. The government of Uzbekistan under President Shavkat Mirziyoyev has invested heavily in developing tourism as a high-growth potential industry, resulting in an increase in international arrivals from approximately 1 million in 2016 to 7 million in 2023.